EVALUATION OF HOWARD COUNTY'S JOURNEY TO BETTER HEALTH PROGRAM. (11th November 2018) - Varghese, R; Borelli, S; Bollino Doyle, C; Hoffman, V; Emery, D; Talbert, K; Butler, T
Abstract: Journey to Better Health (J2BH), funded by Howard County Health Department, is an innovative health education and social support program that builds partnerships with Faith Based Organizations (FBOs) to empower congregants better manage/prevent chronic diseases and reduce hospitalizations. J2BH offers evidence-based chronic-disease prevention and self-management classes such as National Diabetes Prevention Program (NDPP), Hype Down and Chronic Disease Self-Management Program (CDSMP). Enrollees are paired with volunteer community companions for social support. J2BH evaluation assessed program effectiveness and identified strategies for program improvement. Changes in enrollees' health and behavioral outcomes were quantitatively assessed by exploring trends and associations using pre- and post-program data. Interviews with enrollees, community companions and program staff identified program barriers and facilitators. J2BH signed covenants with 9 FBOs in the first 18 months and screened 426 congregants for eligibility. Of those screened, 62% were pre-diabetic, 68% pre-hypertensive/hypertensive and 75% overweight/obese. 10% of eligible congregants enrolled in NDPP, 9% in Hype Down and 4% in CDSMP. Participants improved health outcomes at program completion. 82% of Hype Down enrollees had a reduction in blood pressure levels. 76% of NDPP enrollees reduced/maintained weight, for an average reduction of 3.6%. For CDSMP, Body Mass Index and blood pressure levels showed improvement. All three groups reported improved self-efficacy. Promising practices included leveraging Howard County General Hospital resources, categorizing FBO partnership levels and customizing outreach and services based on need. Recommendations for process improvement included improved advertising, additional ways to motivate program participation, expanding staff size, and refresher/online training for community companions.